Pengaruh E-Book Berbasis Gamifikasi Terhadap Kemampuan Mengenal Bentuk Gemoetri Pada Anak Usia 5-6 Tahun di TK Negeri Pembina 3 Pekanabaru - Aisyah Dianis; Enda Puspitasari; Defni Satria (Departement of Mathematics Education, 2024)
The ability to recognize geometric shapes in TK Negeri Pembina 3 Pekanbaru is still not as expected, therefore a treatment is needed to improve children's ability to recognize geometric shapes using gamification-based e-books. The purpose of this study was to determine and prove the effect of gamification-based e-books on the ability to recognize geometric shapes in children aged 5-6 years at TK Negeri Pembina 3 Pekanbaru. The type of research used is a quantitative experiment with a one group pretest-posttest design. The population in this study were children in class B4 of TK Negeri Pembina 3 Pekanbaru aged 5-6 years totaling 20 people. The sample of this study was 20 people. The sampling technique used in this study was saturated sampling. The data collection technique used by researchers is primary data through observation sheets. Data analysis using t-test. The results showed that there was an increase in the ability to recognize geometric shapes seen from the average acquisition score before and after treatment. The results of data analysis obtained t count 27.264 greater than t table 2.093 from this study can be concluded that gamification-based e-books affect the ability to recognize geometric shapes in children aged 5-6 years at State Kindergarten Pembina 3 Pekanbaru.